Casino 2001 : 1st Quadriënnale voor Hedendaagse Kunst Gent - Belgium - Anton, Saul; Bang Larsen, Lars; Greenberg Rohatyn, Jeanne; Hoet, Jan; Lumpkin, Libby; Matsui, Midori; Scott, Andrea (Gent : SMAK (Stedelijk Museum voor Actuele Kunst) Gent, 2001)
Ackermann, Franz ; Akakce, Haluk ; Albenda, Ricci ; Almond, Darren ; Antille, Emmanuelle ; Bouchet, Mike ; Bowers, Andrea ; Bradley, Slater ; Céspedes, Juan ; Chang, Patty ; Cuevas, Minerva ; Dodge, Jason ; Edmier, Keith ; Edwards, Ben ; Eisinga, Jeroen ; Essenhigh, Inka ; Fairhurst, Angus ; Fawcett, Farrah ; Friedman, Tom ; Fujita, Gajin ; Geers, Kendell ; Grannan, Katy ; Hess, Nic ; Hines, Michelle ; Hirakawa, Noritoshi ; Horowitz, Jonathan ; Jamie, Cameron ; Janssens, Ann Veronica ; Kato, Mika ; Kauper, Kurt ; Korpys, Andree ; Lin, Michael ; Löffler, Markus ; Majerus, Michel ; Manzelli, Margherita ; Marder, Malerie ; Marshall, Maria ; Mehretu, Julie ; Michael, Lucas ; Morris, Sarah ; Morton, Victoria ; Musgrave, David ; Nagai, Mie ; Nemes, Csaba ; Nicolai, Olaf ; Noble, Tim ; Patterson, Richard ; Pearlstein, Alix ; Pfeiffer, Paul ; Reuen, Hannelore ; de Rijke, Jeroen ; Robijns, Gert ; de Rooij, Willem ; Rostovsky, Peter ; Ruilova, Aïda ; Swallow, Ricky ; Szépfalvi, Agnes ; Théron, Didier ; Tuttofuoco, Patrick ; Uklanski, Piotr ; Vari, Minnette ; Webb, Gary ; Webster, Sue ; Olde Wölbers, Saskia ; Xhafa, Sislej
publ. SMAK : zie kast leeszaal
Engels
Nederlands
Exhibition. Casino 2001 : 1st Quadriënnale voor Hedendaagse Kunst. SMAK (Stedelijk Museum voor Actuele Kunst) Gent. 2001-10-28. 2002-01-13
boek
Keywords: U.S.A.